Nanomaterials: leading immunogenic cell death-based cancer therapies - Ma, Changyu; Cheng, Zhe; Tan, Haotian; Wang, Yihan; Sun, Shuzhan; Zhang, Mingxiao; Wang, Jianfeng (Frontiers in Immunology, 2024)
The field of oncology has transformed in recent years, with treatments shifting from traditional surgical resection and radiation therapy to more diverse and customized approaches, one of which is immunotherapy. ICD (immunogenic cell death) belongs to a class of regulatory cell death modalities that reactivate the immune response by facilitating the interaction between apoptotic cells and immune cells and releasing specific signaling molecules, and DAMPs (damage-associated molecular patterns).The inducers of ICD can elevate the expression of specific proteins to optimize the TME (tumor microenvironment). The use of nanotechnology has shown its unique potential. Nanomaterials, due to their tunability, targeting, and biocompatibility, have become powerful tools for drug delivery, immunomodulators, etc., and have shown significant efficacy in clinical trials. In particular, these nanomaterials can effectively activate the ICD, trigger a potent anti-tumor immune response, and maintain long-term tumor suppression. Different types of nanomaterials, such as biological cell membrane-modified nanoparticles, self-assembled nanostructures, metallic nanoparticles, mesoporous materials, and hydrogels, play their respective roles in ICD induction due to their unique structures and mechanisms of action.Therefore, this review will explore the latest advances in the application of these common nanomaterials in tumor ICD induction and discuss how they can provide new strategies and tools for cancer therapy. By gaining a deeper understanding of the mechanism of action of these nanomaterials, researchers can develop more precise and effective therapeutic approaches to improve the prognosis and quality of life of cancer patients. Moreover, these strategies hold the promise to overcome resistance to conventional therapies, minimize side effects, and lead to more personalized treatment regimens, ultimately benefiting cancer treatment.